"Each Council shall appoint a competent person for the borough, hereinafter called "Inspector of Buildings"": The development of building controls in the second decade of the twentieth century - Isaacs, Nigel (Architectural History Aotearoa, 2022)
In 1903 the first edition of the Municipal Handbook of New Zealand was released by the Census and Statistics Office. From then on published biennially, it provided detailed statistical and administrative information on each borough, city, independent town district, and harbour board. This included a brief statistical summary with details of the various activities as well as the names of "Chief Officials," including those responsible for buildings. These included engineers (e.g. Borough Engineer), inspectors (e.g. Building Inspector) and surveyors (e.g. Building Surveyor). From 1910 the numbers of these officials increased, suggesting a growing interest in building controls. The 1915 edition of the Handbook listed 176 municipalities, of which 44 (25%) listed a chief official with a role related to buildings. These included 35 engineers, eight inspectors and one surveyor. The paper explores, based on the Municipal Handbook series, the changing interest of New Zealand local government in the buildings constructed within their boundaries in the second decade of the twentieth century.